1998
DOI: 10.3109/17453679809117614
|View full text |Cite
|
Sign up to set email alerts
|

Choice of implant for internal fixation of femoral neck fractures: Meta-analysis of 25 randomised trials including 4,925 patients

Abstract: We reviewed all randomised trials comparing different implants for treating intracapsular fractures of the hip and, where possible, the data were combined. 25 randomised trials were identified involving 4,925 patients. Screws appeared to be superior to pins. It was not possible to determine the optimum number or type of screws. No advantage was shown for an implant with a side-plate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
65
2
10

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(78 citation statements)
references
References 22 publications
1
65
2
10
Order By: Relevance
“…On clinical grounds, Parker and Blundell [4] meta analyzed 25 randomized trials including 4,925 patients and found it impossible to determine the optimum number or type of screws.…”
Section: Discussion-conclusionmentioning
confidence: 99%
“…On clinical grounds, Parker and Blundell [4] meta analyzed 25 randomized trials including 4,925 patients and found it impossible to determine the optimum number or type of screws.…”
Section: Discussion-conclusionmentioning
confidence: 99%
“…Cut-out tests permit studies of the holding power of osteosynthesis devices of the femoral head independently of the stability of the osteotomy, in a more physiological loading situation than pull-out tests (Richards et al 1990). Pins or nails were reported to have less than optimal clinical results (Parker and Blundell 1998), therefore we chose to test only screw devices. We were unable to detect any significant difference in the holding power of the four different devices, as already reported for pull-out tests (Sjostedt et al 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous kinds of hardware for osteosynthesis of femoral neck fractures have been advocated, but there is no clinical evidence of the superiority of any of them (Parker and Blundell 1998). New devices with more efficient designs are supposed to have a better holding power in the femoral head.…”
mentioning
confidence: 99%
“…Bhandari's meta-analysis showed a higher risk of revision surgery with screw fixation versus a sliding hip screw construct [60••]. Other studies comparing the two constructs have shown no difference in union rates or complications [61]. Until there is more clinical evidence comparing fixation of these fractures, there will be considerable debate regarding which implant is most appropriate.…”
Section: Implant Choicementioning
confidence: 99%